The Effect of Egg-Derived Antibody on Prevention of Avian Influenza Subtype H9N2 in Layer Chicken - Rahimi, Shaban; Salehifar, Ehsan; Ghorashi, Seyed Ali; Grimes, Jesse L.; Torshizi, Mohammad A. Kaimi (International Journal of Poultry Science, 2007)
Avian Influenza (AI) is a contagious disease of poultry which caused by type A influenza virus. In the present outbreak of AI in Iran, the isolates (H9N2) were characterized as a low pathogenic form of the virus. Outbreaks due to H9N2 subtypes have been reported in many countries. Because the common methods of control of outbreaks of AI may not be very effective to prevent and control of this disease, we decided to study the effect of egg derived antibody on reducing morbidity and spread of virus in a population of chickens by using so-called transmission experiments. Birds in test group (which received antibody in drinking water) had lower morbidity (p